“SI-RAJA” ANDROID APPLICATION (ESTIMATED FETAL WEIGHT) IMPROVES MIDWIFE’S ATTITUDE IN MONITORING FETAL GROWTH IN HEALTH CENTERS THROUGHOUT TANJUNGPINANG CITY, RIAU ISLANDS PROVINCE - Darwitri Darwitri; Respatiningrum Respatiningrum; Metasari Sihaloho; Marella Marella (International Journal of Social Science, 2022)
Estimated Fetal Weight is one way to monitor the growth of the fetus in the womb. Along with technology development, Android users can be used as a health educational information medium. This study aims to analyze the effect of using the Si-RAJA Android Application (Estimated Fetal Weight) on the attitude of midwives in monitoring fetal growth at health centers throughout Tanjungpinnag City, Riau Islands Province. This study used a quasi-experiment method with a one-group pretest and posttest design on 30 midwives selected using the proportionate random sampling technique. The data was collected from September to October 2021 at health centers throughout Tanjungpinang City. Data analysis using the Wilcoxon test. There was a significant difference in the attitude before and after using the Si-RAJA android application, with a p-value of 0.000. As a result, it is hoped that midwives can monitor growth, provide counseling to pregnant women about fetal growth, and provide treatment as early as possible if abnormal fetal weight estimates are found.